PENGEMBANGAN LKPD MATA PELAJARAN BAHASA INDONESIAPADAELEMEN MENYIMAK DALAM KURIKULUM MERDEKA DI KELAS V SDN06SITIUNG - Dodi Widia Nanda; Gunawan Ali; Novita Wulandari (STKIP Subang, 2024)
Thisresearchisbased on thelackof teachingmaterialsfor theindependentcurriculumthatareinaccordancewiththeneedsoftheschool.SDN06Sitiu ng needsteachingmaterials,oneofwhichistheIndonesianLanguageLKPD inclass V. So the effort made is to develop the LKPD of Indonesian Language Subject ontheListeningElementintheIndependentCurriculuminClassVwhichisvalid, practical,andeffective.ThistypeofresearchisResearchandDevelopment researchwhichusestheADDIEdevelopmentmodelwhichhasseveralstages, namely(Analysis,Design,Development,Implementation,Evaluation).The assessmentinstrumentwascarriedoutbythreevalidators,namelycontent validators, language validators and media validators. Filling out the instrument sheet usesavalidationsheetforvalidatorsandapracticalitysheetassessedby practitioners.The results obtained from the development of the Indonesian Language SubjectLkpdontheListeningElementintheIndependentCurriculuminClassVofSDN06 Sitiung are from the resultsof the validator obtained an average of 83.3% witha veryvalidcategory,thepracticalityscoreobtainedan averagescoreof80.5%with a very practical category, and the